2012
DOI: 10.1007/s13277-012-0601-2
|View full text |Cite|
|
Sign up to set email alerts
|

Matrix metalloproteinase 9 expression and prognosis in colorectal cancer: a meta-analysis

Abstract: Matrix metalloproteinase-9 (MMP-9) is an important member of the matrix metalloproteinase family and is considered to be involved in the invasion and metastasis of cancer cells. Many studies were published to assess the prognostic role of MMP-9 overexpression in patients with colorectal cancer, but the findings from those studies were inconsistent. We searched eligible studies in Pubmed, Embase, and Web of Science databases. Thirteen studies with a total of 2, 390 CRC patients were finally included into the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 31 publications
7
30
1
Order By: Relevance
“…In view of its broad functions in tumor invasion and metastasis, MMP9 may be a valuable prognostic biomarker in glioma. Previous meta-analysis has shown a significant correlation between high expression levels of MMP9 and poor prognosis in gastric cancer (18), breast cancer (19), non-small cell lung cancer (20) and colorectal cancer (21). MMP9 has also been implicated in the invasion and metastasis of head and neck squamous cell carcinoma (9).…”
Section: Discussionmentioning
confidence: 99%
“…In view of its broad functions in tumor invasion and metastasis, MMP9 may be a valuable prognostic biomarker in glioma. Previous meta-analysis has shown a significant correlation between high expression levels of MMP9 and poor prognosis in gastric cancer (18), breast cancer (19), non-small cell lung cancer (20) and colorectal cancer (21). MMP9 has also been implicated in the invasion and metastasis of head and neck squamous cell carcinoma (9).…”
Section: Discussionmentioning
confidence: 99%
“…58 A meta-analysis of laryngeal cancers demonstrated that MMP2 expression was higher in cases with lymph-node metastasis, and suggested that upregulation of MMP2 could be instrumental in tumorigenesis, progression, and prognosis in laryngeal cancer. 127 Zhang et al investigated MMP2, -3, and -9 single-nucleotide polymorphisms in esophageal SCC. 128 The authors suggested that MMP2 -1306TT and MMP9 -1562CC single-nucleotide polymorphisms correlated with increased esophageal SCC risk and significantly high death odds.…”
Section: Mmps As Tumor Biomarkersmentioning
confidence: 99%
“…Activated MMP-2 is located in the protruding section of the cell-penetrating matrix. Its activation facilitates the passage of tumor cells through the ECM and the basal membrane of the blood vessel wall, thus promoting invasion of tumor cells (28). In addition, MMP-2 and -9 are gelatinases; thus, their role in the degradation of gelatin leads to the release of signaling molecules from the ECM that aid cell migration and angiogenesis (29).…”
Section: Introductionmentioning
confidence: 99%